Association between weight-adjusted waist index and obstructive sleep apnea among adults in the United States: data from NHANES (2005–2008 and 2015–2018) - Qi Zhang; Yong Zhai; Jing Wang; Xu Han; Wurong Si; Yizhong Zhou (Journal of International Medical Research)
Objective We aimed to examine the relationship between the weight-adjusted waist index (WWI) and obstructive sleep apnea (OSA), a condition often caused by obesity, which remains unclear. Methods In this cross-sectional study, we analyzed data from the National Health and Nutrition Examination Survey among adults in the United States (US) aged 20 to 65 years, covering the periods 2005 to 2008 and 2015 to 2018. The study included 8278 participants; we used multivariate logistic regression, restricted cubic splines, and subgroup analyses to explore the relationship between WWI and OSA. Results After adjusting for all covariates, each unit increase in WWI was associated with a 30% increase in OSA prevalence (odds ratio = 1.30, 95% confidence interval: 1.20–1.40). Conclusions These findings suggest that WWI, an index reflecting abdominal obesity, can provide important insights into OSA risk assessment. Its strong association with OSA highlights its potential utility in predicting OSA prevalence, particularly among diverse subpopulations. The WWI was associated with a higher prevalence of OSA among US adults and may serve as a valuable tool for risk assessment, early screening, and intervention strategies in clinical practice.